Influence of Brewing Time and Temperature on Antioxidant Activity of Pedada (Sonneratia caseolaris) Fruit Peel Extract as a Potential Functional Drink - Muhammad Fauzan; Laksmi Sulmartiwi; Eka Saputra (Universitas Airlangga, 2022)
Pedada (Sonneratia caseolaris) are plants that live in the mangrove ecosystem. The fruit of the pedada plant is round, has stemmed tip, base is wrapped by petal, non-toxic and edible. The flesh of the pedada fruit is used as syrup, but the peel is considered as waste. On the other hand, pedada fruit peel contains antioxidant activity compound, such as phenol, tannin, and flavonoid. A way to process the pedada fruit skin into a functional drink is required so that it has economic value. The purpose of this study was to determine the effect of different brewing temperatures and duration on the antioxidant activity of pedada (Sonneratia caseolaris) peels extract. The research method used was experimental with Factorial Completely Randomized Design (CRD) as the experimental design. The factors used are temperature (70○C, 85○C, and 100○C) and time (5, 10, and 15 minutes) with 3 replications. The main parameter observed was the extract’s antioxidant activity. Supporting parameters observed were water content, total phenolic content, and antioxidant activity of pedada fruit peel. Data analysis used was Two Way Analysis of Variance (Anova) and followed by Honest Significantly Difference (HSD) by 5%.The results showed that the increase in temperature and duration increased the antioxidant activity of the pedada fruit peel extract. The best treatment was obtained by 100○C treatment for 10 minutes which was not significantly different from 100○C treatment for 5 minutes and 85○C for 15 minutes. In addition, there was an increase in antioxidant activity of 12,10% from the best treatment compared to the control treatment.